Positive expression of miR-361-5p indicates better prognosis for breast cancer patients - Cao, Zhi-Gang; Huang, Yan-Ni; Yao, Ling; Liu, Yi-Rong; Hu, Xin; Hou, Yi-Feng; Shao, Zhi-Min (Journal of Thoracic Disease; Vol 8, No 7 (July 05, 2016): Journal of Thoracic Disease, 2016)
Background: MicroRNA-361-5p (miR-361-5p) has been reported to be tumor suppressor in colorectal, gastric and prostate cancer, but as an oncogene in cervical cancer. No previous research has focused on the expression of miR-361-5p and its exact prognostic role in breast cancer (BC). Methods: In this study, a tissue microarray (TMA)-based miRNA detection in situ hybridization (ISH) with LNA probe was used to detect miR-361-5p expression in 375 BC tissue. The expression level of miR-361-5p in BC and its potential prognostic value was investigated. Results: Positive miR-361-5p staining was observed in 78.7% (N=295; 78.7% positive, 21.3% negative) in the 375 cases. The clinical outcome of patients with positive miR-361-5p expression [median disease-free survival (DFS) time 95.52 months] was significantly better than that of patients (median DFS time 82.33 months) with negative miR-361-5p expression (P=0.002). Moreover, the prognostic value of miR-361-5p was most significant among patients with triple-negative breast cancer (TNBC) for DFS (P=0.004). Conclusions: These results indicated that miR-361-5p expression is an independent predictive factor for better prognosis in BC.